The Use of Matrix Heat Pipe as Photovoltaic Cooler - Rahmat Subarkah; Tatun Hayatun Nufus; Rahmat A Setiawan; Achmad Subakri; Wisnu Tri Nur Kahfi; Try Laksono Prasetyo (Institut Teknologi Sepuluh Nopember, 2014)
The high surface temperature can decrease the efficiency of solar cells. This research aim is to decrease the temperature of the solar cell using the matrix heat pipe as a heat conductor. The study began by constructing a matrix of heat pipes. ¼ inch diameter copper tubing (6.3 mm) pressed until it reaches a thickness of 4.2 mm. Heat pipe using 10 mesh wire screen and water as the working fluid as about 20% of the volume of the pipe. Twenty-five heat pipes arranged matrix configuration. The pipes were vacuumed to pressure 0.0799 bar. Flat heat pipe were placed below the surface of the solar cell. Phase change liquid-gas of work fluid on the heat pipe occurs at saturated temperature of 42ºC. This heat pipe reduces surface temperature of solar cell as 8ºC and increase efficiency of solar cell as 1.6%.